Exploring Breastfeeding Mothers’ and Lactation Consultants’ Experiences of Lactation Consultancy Throughout the Restrictions Put in Place Due to the COVID-19 Pandemic [version 2; peer review: 2 approved] - Anne Matthews; Anna Connolly (HRB Open Research)
Background Breastfeeding rates in Ireland are among the lowest in the world. Lactation consultancy provides mothers with support and information on how to cope with any challenges they encounter. There is emerging evidence that COVID-19 restrictions impacted access to and the quality of breastfeeding support. The aim of this study was to explore breastfeeding mothers’ and lactation consultants’ experiences of breastfeeding support throughout the COVID-19 restrictions in Ireland. It also aimed to explore what adaptations had to be made to the delivery of lactation consultancy and how these changes impacted mothers’ experiences of breastfeeding support. Methods A qualitative research design was chosen. Semi-structured interviews were conducted with eight participants, three breastfeeding mothers and five lactation consultants. Interviews were conducted online via Zoom, audio-recorded and transcribed. The data were analysed using thematic analysis. Results Five key themes were identified: ‘Lack of Support’, ‘Adapting to COVID-19 Restrictions’, Emotional Response to COVID-19 and Restrictions’, Vaccination against SARS-CoV-2 as a Barrier to and Facilitator of Support’ and Inconsistency of Lactation Support Across Ireland’. Both lactation consultants and mothers identified similar issues however, slight variations within lactation consultants' perceptions of mothers’ and mothers’ attitudes towards online services were seen. An notable finding was the lack of support in hospitals pre-COVID-19. Conclusions Both mothers’ and lactation consultants’ experiences of lactation consultancy were impacted by the COVID-19 restrictions. Although exacerbated by COVID-19, the lack of support in hospitals existed before COVID-19. Provision of better breastfeeding support is required. Increased availability of lactation consultants and the implementation of breastfeeding rooms within hospitals is required in addition to debrief counselling sessions for lactation consultants. Further research is required to understand the unavailability of lactation consultants in hospital settings and to identify how to manage breastfeeding support in future emergency situations.